Citrus leaf disease detection by image processing - Chowdhury, Mahir Faisal; Nondi, Amit; Zaman, Fardin; Akhter, Sium Ibn; Pathan, Tanjina Bilma (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.